Morningside heights ebook A novel. - Henkin, Joshua (2021)
A New York Times Book Review Editors' Choice Book • When Ohio-born Pru Steiner arrives in New York in 1976, she follows in a long tradition of young people determined to take the city by storm. But when she falls in love with and marries Spence Robin, her hotshot young Shakespeare professor, her life takes a turn she couldn’t have anticipated.   Thirty years later, something is wrong with Spence. The Great Man can’t concentrate; he falls asleep reading The New York Review of Books . With their daughter, Sarah, away at medical school, Pru must struggle on her own to care for him. One day, feeling especially isolated, Pru meets a man, and the possibility of new romance blooms. Meanwhile, Spence’s estranged son from his first marriage has come back into their lives. Arlo, a wealthy entrepreneur who invests in biotech, may be his father’s last, best hope. Morningside Heights is a sweeping and compassionate novel about a marriage surviving hardship. It’s about the love between women and men, and children and parents; about the things we give up in the face of adversity; and about how to survive when life turns out differently from what we thought we signed up for.